2021
DOI: 10.3233/jifs-212015
|View full text |Cite
|
Sign up to set email alerts
|

A generalized deep learning framework for automatic rheumatoid arthritis severity grading

Abstract: Knee rheumatoid arthritis (RA) is the highly prevalent, chronic, progressive condition in the world. To diagnose this disease in the early stage in detail analysis with magnetic resonance (MR) image is possible. The imaging modality feature allows unbiased assessment of joint space narrowing (JSN), cartilage volume, and other vital features. This provides a fine-grained RA severity evaluation of the knee, contrasted to the benchmark, and generally used Kellgren Lawrence (KL) assessment. In this research, an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Following that, the computer will arrive at a conclusion by doing several assessments. The expert system is computer software designed from intelligent machines that is best suited for real-time domains or applications [ 41 , 42 ]. This domain is developed to identify real-world applications in more than 70 percent of cases [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following that, the computer will arrive at a conclusion by doing several assessments. The expert system is computer software designed from intelligent machines that is best suited for real-time domains or applications [ 41 , 42 ]. This domain is developed to identify real-world applications in more than 70 percent of cases [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…More et al ( 22 ) introduced a DL model named ResNet50 for assessing the severity of RA in the knee, relying on the Kelgren Lawrence (KL) classification system, using MRI T1W, T2W and PD sequences. The study demonstrated a high level of accuracy at 96,85%, precision of 98,31%, area under curve (AUC) of 0,98 and a mean absolute error (MAE) of 0,015.…”
Section: Applications Of Artificial Intelligence Based On Mri In Rheu...mentioning
confidence: 99%
“…The fundamental stages of an AI algorithm are illustrated in Figure 2 . From the image acquisition to the last stage of result analysis, image processing is essential, undergoing multiple stages before reaching a diagnosis ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the basic algorithm, simulation investigation revealed that the hybrid VM allocation saved 72 percent of power when delivering quality service [13,14]. Jiang [15] suggested a data ABC (Ant Bee Colony) energy model for making VM consolidation decisions based on global optimization.…”
Section: Related Workmentioning
confidence: 99%